Assessment of physical activity of pupils in two selected junior high schools in the Podkarpacie - Grzegorczyk, Joanna; Mazur, Ewa; Domka, Ewa (European Journal of Clinical and Experimental Medicine, 2008)
<span style="color: #010101; font-family: Lato, sans-serif; font-size: 14px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-align: justify; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">Physical activity is the basic element of the healthy lifestyle. It is important at every stage of human life, however, it is particularly crucial in childhood and youth because it conditions the proper physical, psychological and social development. The regular physical activity is of benefit to human organism, allows to retain good physical fitness and condition, prevents development of civilisational diseases and bears a positive influence on the human psyche. Despite that many advantages resulting from physical activity, people often do not go in for it. This paper aims at evaluating the physical activity in the group of children aged 14 to 16. Survey has been conducted in two of the Junior High Schools in Lutna (Malopolskie province) and in Reeszéw in 2007. Survey involved 199 students of the third grade of the Junior High School. In the examined group there were 101 boys and 98 girls. Questionnaire comprising 37 self-prepared questions has been a survey tool. Students recon that physical activity contributes to their well-being. Nearly 90 percent of the respondents takes up sport activities in their leisure time. 36.2 percent of the respondents is physically active 1 to 4 days a week for hour or less, 27.6 percent 1 to 4 days a week for over an hour. The rest of the respondents are physically active 5 to 7 days a week for over an hour or less. The most popular sport disciplines are as following: team sports, cycling, jogging. The level of physical activity is greater with boys than girls. Among people who do not participate in PE classes girls constitute the majority. Parents and teachers are obliged to conduct proper educational actions in order to motivate the youth (especially fair sex) to participate in active leisure activities more frequently.